Intrahepatic Cholestasis due to Citrin Deficiency - Stilwell, Maria do Rosário (2020)
We report a case of Neonatal Intrahepatic Cholestasis due to Citrin Deficiency in a 2-month-old female of Chinese descent who presented with jaundice and acholic stool. She had poor weight gain, axial hypotonia and large anterior fontanelle with no dysmorphia or hepatosplenomegaly. Laboratory findings showed cholestasis, elevated transaminases, hypoalbuminemia, prolonged prothrombin time, anaemia and galactosuria. Obstructive, infectious and genetic causes (Allagille syndrome, alpha-1-antitrypsin deficiency, cystic fibrosis) were excluded, as well as galactosemia. Plasma amino acids chromatography exhibited elevation of citrulline, tyrosine, methionine and threonine, raising a strong suspicion of Citrin Deficiency. The patient was started on a lactose-free formula with medium-chain triglycerides and fat-soluble vitamins, with rapid clinical and laboratory improvement. Genetic analysis confirmed compound heterozygosity in the SLC25A13 We emphasize the importance of considering this hypothesis in the differential diagnosis of neonatal cholestasis, especially in patients of Asian origin, given the possibility of therapeutic intervention and prevention of complications.